Why do new members stop attending health and fitness venues? The importance of developing frequent and stable attendance behaviour. (November 2020) - Rand, Matthew; Goyder, Elizabeth; Norman, Paul; Womack, Robert
Abstract: Objectives: Attendance at health and fitness venues often declines dramatically during the first year of membership. The present study sought to identify factors associated with continued attendance in new members. Methods: A secondary data analysis was conducted on the attendance data of 1726 new members of a health and fitness organisation over the first 12 months of their membership. Associations were assessed between members' frequency and pattern of attendance during the first quarter of their membership, age, gender, and home location and their attendance levels in the fourth quarter after joining. Results: There was a significant reduction in the frequency of attendance over time from a mean of 7.48 times in the first month to a mean of 0.92 in the 12th month after joining. Older age, starting membership in the autumn or spring, frequency of attendance in the first quarter and stability of the context of attendance (i.e., same time and location) in month three were all significantly associated with increased attendance levels in the fourth quarter. Conclusions: The findings indicate that new members' early attendance behaviour, in terms of the frequency and the stability of attendance, may be important for supporting continued attendance at health and fitness venues. Interventions to increase longer-term attendance and, in turn, physical activity, should focus on promoting regular and consistent attendance, especially in terms of day, time and location, early on in individuals' membership of health and fitness venues. Highlights: Only 22% of members attend a health and fitness venue after a year of membership. Older age, males, early attendance and context stability correlate with continued attendance. Interventions are needed to promote early frequent and stable attendance to increase PA.